Plant diversity, compositional turnover, and suitability screening across green open spaces in Semarang District, Indonesia - DEWI RAHMAWATI; FAUZAN RAFI WICAKSONO; HAFIZH MUHAMAD ZEN; HANIFA SABILA RAHMA; RAISA NOOR SAFIRA; WIDHI HIMAWAN; ARU DEWANGGA; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rahmawati D, Wicaksono FR, Zen HM, Rahma HS, Safira RN, Himawan W, Dewangga A, Setyawan AD. 2026. Plant diversity, compositional turnover, and suitability screening across green open spaces in Semarang District, Indonesia. Biodiversitas 27 (5): d270538. https://doi.org/10.13057/biodiv/d270538. Urban green spaces depend on plant composition as well as area, yet district-scale assessments integrating floristic richness, cross-site turnover, and transparent suitability screening remain limited in Indonesia. We inventoried plants at six purposively selected public green spaces in Semarang District, Central Java, in September 2024. Presence records were summarized as taxon and family richness, pairwise composition was compared using the incidence-based Sørensen coefficient, and 194 recorded plant taxa were screened using 23 silvicultural, management, aesthetic, and public-safety criteria. Tree architecture and literature-supported shade and windbreak potential were summarized for the reconciled tree subset. The inventory comprised 194 plant taxa from 62 families; three records were retained above species level (Areca, Croton, and Pteridophyta). Asteraceae (19 taxa), Poaceae (17), and Fabaceae (16) were the richest families. Raw site richness ranged from 33 taxa at GOS Ungaran Barat to 77 at Taman Serasi, and Sørensen similarity ranged from 13.2% to 40.0%, indicating strong compositional differentiation. Suitability totals ranged from 35 to 46; 156 taxa (80.4%) were classified as high and 38 (19.6%) as medium, with no low class. After reconciliation of the architecture dataset, 55 unique tree taxa represented 11 recognized architectural models; 34 were literature-supported shade candidates and 29 windbreak candidates. These are screening results rather than validated performance estimates. Because sites were purposively selected and survey effort, abundance, and site area were not standardized, the study provides a comparative management baseline rather than a district-wide statistical estimate. Management should retain inter-site compositional complementarity and combine screening scores with growth form, local occurrence, safety, and maintenance capacity.